Eş ‘Ari’nin Makalat’ında haricilerin sınıflandırılması ve öne çıkan görüşleri - Haberli, Mehmet (My University, 2006)
Hz. Muhammed’in vefatının ardından meydana gelen bir takım ihtilaflar ve başka sebepler neticesinde fırkalar teşekkül etmeye başlamıştır. Zamanla bu fırkaları ele alan kitaplar yazılmaya başlanmıştır. Mezheplere dair eser yazan müelliflerin başında Ebû’l Hasan el- Eş’ari gelmektedir. Makâlat’ül İslamiyyin adlı eserinde ele almış olduğu fırkalardan birisi Haricîler’dir. Bu fırka Sıffın savaşı sırasında ortaya çıkmıştır.Hz. Aliye karşıya gelmiş ve ondan ayrılmışlardır. Tekfirci bir zihniyete sahip olan bu fırka hakkında, Makâlat’ta ayrıntılı bilgi verilmekte, Haricîlerin kendi içlerinde ayrıldığı talî fırkalar olabildiğince anlatılmaya çalışılmıştır. Bu çalışmamızda Eş’ari’nin Makalat’ında Haricîleri nasıl ele aldığını, kaç sınıfa böldüğünü ve öne çıkan görüşlerini anlatmaya çalıştık.

The systematization of Sunni theology in the tenth century was done in reaction to the emergence of heterodox schismatic groups in previous centuries. The founder of Ash'ariyyah, Abu al-Hasan (873-935) wrote a number of important books which became the foundation of Ash'arite theology such as the Kitab al-Ibanah (The Book of Elucidations) and also an extensive work on the views of various Islamic schools and sects called Maqalat al-Islamiyyin (Doctrines of the Muslims). The one of this İslamic school in Maqalat al-Islamiyyin is Kharjits. The origin of Kharijism lies in the first Islamic civil war: a struggle for political supremacy over the Muslim community in the years following the death of prophet Muhammad. Kharijite theology was a form of radical fundamentalism, preaching uncompromising observance of the teachings of the Qur'an in defiance of corrupt authorities. With this study tried to describe the origins, Beliefs and practices of Kharijism in Maqalat al-Islamiyyin.
Keywords: İslam Dini